2023
DOI: 10.1007/s00005-023-00677-w
|View full text |Cite
|
Sign up to set email alerts
|

Omics are Getting Us Closer to Understanding IgA Nephropathy

Abstract: During the last decade, thanks to omics technologies, new light has been shed on the pathogenesis of many diseases. Genomics, epigenomics, transcriptomics, and proteomics have helped to provide a better understanding of the origin and heterogeneity of several diseases. However, the risk factors for most autoimmune diseases remain unknown. The successes and pitfalls of omics have also been observed in nephrology, including immunoglobulin A nephropathy (IgAN), the most common form of glomerulonephritis and a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 114 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…Besides, previous studies shown the association of IgAN with genetic variations in the HLA gene family, as well as other genes like TAP1/PSMB and DEFA across diverse populations. These genetic factors may contribute to the pathogenesis of IgAN and its complications, including TMA (36)(37)(38). Still, endothelial damage induced by C5b-9 leads to increased expression of the von Willebrand factor gene, promoting platelet activation and the formation of thrombi (26).…”
Section: Genetics Of Tma In Iganmentioning
confidence: 99%
“…Besides, previous studies shown the association of IgAN with genetic variations in the HLA gene family, as well as other genes like TAP1/PSMB and DEFA across diverse populations. These genetic factors may contribute to the pathogenesis of IgAN and its complications, including TMA (36)(37)(38). Still, endothelial damage induced by C5b-9 leads to increased expression of the von Willebrand factor gene, promoting platelet activation and the formation of thrombi (26).…”
Section: Genetics Of Tma In Iganmentioning
confidence: 99%
“…The clinical presentation of IgAN can vary greatly, encompassing a wide spectrum of manifestations. These can range from no apparent symptoms, such as the presence of asymptomatic hematuria and proteinuria, to gross hematuria accompanied by a rapid decline in kidney function [3]. Renal biopsy is considered the gold standard for diagnosis of IgAN.…”
Section: Introductionmentioning
confidence: 99%